Kinase Activity Mapping from Proteome Phosphorylation Data in a Breast Cancer Cohort - Castilla Maldonado,Ignacio (2025)
Phosphorylation is one of the main post-translational modifications (PTMs) regulating protein function, where kinases reversibly add phosphate groups to specific amino acid residues (phosphosites). Kinase activity is altered in breast cancer (BC), resulting in loss of regulation of several cellular processes. Phosphoproteomics emerges as a powerful approach for profiling samples at phosphosite level, with the potential to identify kinase-driven BC subtypes and guide subsequent treatments. The aim of the present master’s thesis was to conduct a functional analysis of data-independent acquisition (DIA) mass spectrometry phosphoproteomic data from a BC cohort. The data filtering strategy was intended to prioritise low-abundance phosphosites. A total of 50 phosphosites were found to be significantly different between the clinical groups, and enabled partial separation of lobular and ductal BC samples in a two-component probabilistic principal component analysis (PPCA). Phosphosite-to-kinase inference was conducted using PTM-Signature Enrichment Analysis (PTM-SEA) and the Integrative iNferred Kinase Activity (INKA) tool. PTM-SEA inferred 17 kinases that showed differential activity. INKA was successfully adapted to the DIA neuronal network (DIA-NN) workflow and inferred 5 kinases that were found significantly different. No group-specific kinase activity was detected when using either PTM-SEA or INKA, and samples did not cluster into their clinical groups in PPCAs based on the significantly different kinase activities inferred from the tools. Nevertheless, PTM-SEA results allowed for unsupervised clustering of sample groups in correspondance with clinical parameters and offered both positive and negative enrichment scores, providing a more comprehensive analysis than INKA.
Keywords: Breast cancer; Phosphoproteomics; Phosphosites; Phosphosite-to-kinase inference; PTM-SEA; INKA; Pharmaceutical technology